Nuclear Medicine for Precisiondiagnosis of Malignant Melanoma: A Literature Review - Karinnia Karinnia; Linda Julianti Wijayadi; Kelvin Kelvin (GLOBAL HEALTH SCIENCE GROUP, 2025)
Malignant melanoma (MM) is a rare skin cancer that is increasing constantly. It accounts for the most cause of death of all skin cancer. High accuracy in MM staging is crucial to give exact information about the prognosis and facilitate the use of the most effective therapy available. The gold standard for skin cancer diagnosis is tissue biopsy, therefore precisely detecting the primary tumor site is crucial. It has high risk of dissemination to regional lymph nodes and visceral organs. Lymph node involvement and distant metastasis are the key prognostic value of MM. Nuclear medicine has been used to detect various primary and metastatic cancer including skin cancer. The aim of this literature review is to discuss about the role of nuclear medicine specifically positron emission tomography (PET), single-photon emission tomography (SPECT), and planar gamma imaging for the diagnosis of MM. We gather literature searches and books related using combined keywords such as “gamma camera”, “SPECT”, “PET”, “malignant melanoma”, “histopathology”. The data we use are limited to 10 years of this review article. Nuclear medicine technique, such as lymphoscintigraphy using gamma camera or SPECT/CT is recommended for early stage of MM, while PET/CT is recommended and have high sensitivity for advance stage of MM and evaluating disease recurrence. Utilising nuclear medicine to aid in acurate diagnostic of MM will give opportunity of a better outcome.